"We're all mad": Simon Critchley interview. Issue 4 (December 2018) - Critchley, Simon; Goodman, David; Orange, Donna
Abstract This article is an edited transcript of an interview with Simon Critchley conducted by David Goodman and Donna Orange at the New School in New York City on 24th February 2017. The focus of the interview was on the intersections between psychoanalysis and politics in Critchley's work. Specific attention was given to Critchley's scholarship regarding Emmanuel Levinas, the persistence of the autonomy orthodoxy, and his understanding of sublimation and a superego II, along with careful consideration of how humor, among other things, may be utilized with regard to ethical political action and motivation.